Three-phase multilevel inverter for grid-connected distributed photovoltaic systems based in three three-phase two-level inverters - Fernao Pires, Vitor (2019)
A multilevel three-phase voltage source inverter (VSI) for distributed grid-connected photovoltaic system is proposed in this paper. This multilevel inverter is based on a new topology using three three-phase two-level VSIs ((TVSI)-V-3) with isolation transformer. The photovoltaic panels are connected at the DC side of each three-phase VSI. The three-phase VSIs AC sides are connected to the three-phase isolation transformer with primary open-end windings, ensuring multilevel operation. The (TVSI)-V-3 can be modulated using existing multilevel Pulse Width Modulation (PWM) schemes. A control system designed to ensure the transfer of the energy generated by the PV generators to the grid is also presented, together with a Phase Disposition PWM (PDPWM) adapted for the multilevel (TVSI)-V-3. Tests of the grid-connected PV multilevel (TVSI)-V-3 will be shown through simulation and experimental results. Several results obtained from experiments confirm the expected characteristics of the multilevel (TVSI)-V-3 photovoltaic system.